HUBUNGAN HIPERTENSI DENGAN SKOR GENSINI PASIEN PENYAKIT JANTUNG KORONER STABIL DI RSUP DR. M. DJAMIL PADANG TAHUN 2021-2022 - Prima Adelin; Indriana Mukti; Yuni Handayani; Dian Puspita; Debie Anggraini; Ruhsyahadati (Yayasan Nusantara Hasana Berdikari, 2024)
Hypertension is one of the risk factors that can cause Coronary Artery Disease (CAD) beginning with the formation of atherosclerotic plaques that can cause arterial stenosis can be assessed using the gensini score. This study aims to determine the relationship between hypertension and gensini scores of stable coronary heart disease patients at Dr. M. Djamil Padang Hospital in 2021-2022. This type of research is a cross-sectional approach using medical record data. An affordable population of research is stable coronary heart disease patients who underwent coronary angiography at Dr. M. Djamil Padang Hospital in 2021-2022 with 52 samples using consecutive sampling techniques. Univariate analysis is displayed in the frequency distribution and average distributions while bivariate analysis is performed using the rank spearman test. The results showed that most coronary artery disease patients are men ≥ 45 years (53.8%) and women ≥ 55 years (26.9%), the majority of patients are men (59.6%), 67.3% of patients do not have a family history, the average systolic blood pressure is 152.42 mmHg, the average diastolic blood pressure is 85.98 mmHg, the average gensini score is 63.33. There is a significant correlation between systolic blood pressure and diastolic blood pressure with gensini score. (p<0.05).